2021
DOI: 10.1111/csp2.578
|View full text |Cite
|
Sign up to set email alerts
|

Developing a nature recovery network using systematic conservation planning

Abstract: Conservation area networks in most countries are fragmented and inadequate. To tackle this in England, government policies are encouraging stakeholders to create local‐level nature recovery networks. Here, we describe work led by a wildlife organization that used the systematic conservation planning approach to identify a nature recovery network for three English counties and select focal areas within it where they will focus their work. The network was based on identifying core zones to maintain current biodi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…If these on-site units which risk being unenforceable were instead provided via off-site biodiversity offsets, the total area of offsetting required to deliver BNG could rise by a factor of four, drawing substantially more investment into delivering biodiversity gains on private land via the market for biodiversity units. If these investments were directed towards priority habitat landscapes within the LPAs proposed Local Nature Recovery Networks (Smith et al 2022), the potential biodiversity benefits could be further enhanced by improving ecological characteristics, such as connectivity, which are poorly addressed in the Metric.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If these on-site units which risk being unenforceable were instead provided via off-site biodiversity offsets, the total area of offsetting required to deliver BNG could rise by a factor of four, drawing substantially more investment into delivering biodiversity gains on private land via the market for biodiversity units. If these investments were directed towards priority habitat landscapes within the LPAs proposed Local Nature Recovery Networks (Smith et al 2022), the potential biodiversity benefits could be further enhanced by improving ecological characteristics, such as connectivity, which are poorly addressed in the Metric.…”
Section: Discussionmentioning
confidence: 99%
“…A recent government report suggested that once BNG becomes mandatory, up to 50% of all of the biodiversity units delivered by the policy would be from off-site offsets (EFTEC 2021). As a result, BNG has been referenced as a potentially important revenue stream for funding the implementation of England's proposed new Local Nature Recovery Strategies (Smith et al 2022) -although it should be noted that biodiversity compensation is a defensive expenditure (i.e. making up for an equal and opposite loss elsewhere) and so these investments are not seeking to improve the state of England's nature, but merely to prevent ongoing declines from development.…”
Section: Introductionmentioning
confidence: 99%
“…If on‐site units at risk of being unenforced were instead provided off‐site, the total area of offsetting required to deliver BNG could rise by a factor of 4, drawing substantially more investment into delivering biodiversity gains on private land via the market for biodiversity units. If these investments were directed toward priority habitat landscapes in the LPAs proposed “local nature recovery networks” (Smith et al., 2022), the potential biodiversity benefits could be further enhanced by improving ecological characteristics, such as connectivity, which are poorly addressed in the BNG metric. A challenge to increasing off‐site gains, however, is locating areas where gains can be achieved by creating or enhancing the habitat types.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that once BNG becomes mandatory, up to 50% of all biodiversity units delivered by the policy would be off‐site (EFTEC, 2021). Thus, the BNG policy could be an important revenue stream for funding the implementation of England's proposed new Local Nature Recovery Strategies (Smith et al., 2022). However, biodiversity compensation is a defensive expenditure (i.e., making up for an equal and opposite loss elsewhere), so these investments are not made to improve the state of nature, but to prevent ongoing biodiversity declines and compensate for biodiversity losses resulting from development.…”
Section: Introductionmentioning
confidence: 99%
“…Granular data on species distributions also serve as input for systematic conservation planning. A recent attempt to carry out a systematic conservation plan in southern England was forced to use habitat classes rather than species data because most English species records are restricted to urban and protected areas (Smith et al 2021). award 2025118.…”
Section: Combining Metacommunity Theory With Novel Community Datamentioning
confidence: 99%